Analysis of inter- and intra fractional partial bladder wall movement using implanted fiducial markers - Nishioka, Kentaro (Radiat Oncol, 2017)
BACKGROUND: Current adaptive and dose escalating radiotherapy for muscle invasive bladder cancer requires knowledge of both inter-fractional and intra-fractional motion of the bladder wall involved. The purpose of this study is to characterize inter- and intra-fractional movement of the partial bladder wall using implanted fiducial markers and a real-time tumor-tracking radiotherapy system. METHODS: Two hundred fifty one sessions with 29 patients were analysed. After maximal transurethral bladder tumor resection and 40 Gy of whole bladder irradiation, up to six gold markers were implanted transurethrally into the bladder wall around the tumor bed and used for positional registration. We compared the systematic and random uncertainty of positions between cranial vs. caudal, left vs. right, and anterior vs. posterior tumor groups. The variance in intrafractional movement and the percentage of sessions where 3 mm and 5 mm or more of intrafractional wall movement occurring at 2, 4, 6, 8, 10, and at more than 10 min until the end of a session were determined. RESULTS: The cranial and anterior tumor group showed larger interfractional uncertainties in the position than the opposite side tumor group in the CC and AP directions respectively, but these differences did not reach significance. Among the intrafractional uncertainty of position, the cranial and anterior tumor group showed significantly larger systematic uncertainty of position than the groups on the opposite side in the CC direction. The variance of intrafractional movement increased over time; the percentage of sessions where intrafractional wall movement was larger than 3 mm within 2 min of the start of a radiation session or larger than 5 mm within 10 min was less than 5%, but this percentage was increasing further during the session, especially in the cranial and anterior tumor group. CONCLUSIONS: More attention for intrafractional uncertainty of position is required in the treatment of cranial and anterior bladder tumors especially in the CC direction. The optimal internal margins in each direction should be chosen or a precise intrafractional target localization system is required depending on the tumor location and treatment delivery time in the setting of partial bladder radiotherapy.